Recent advances in applications of nonradical oxidation in water treatment: Mechanisms, catalysts and environmental effects. (25th October 2021) - Dong, Jie; Xu, Weihua; Liu, Shaobo; Du, Li; Chen, Qiang; Yang, Ting; Gong, Youzi; Li, Meifang; Tan, Xiaofei; Liu, Yunguo
Abstract: Nonradical oxidation in advanced oxidation processes (AOPs) has been extensively applied in contaminants elimination from aqueous solutions. Since nonradical oxidation was first proposed in the Gif system in 2001, high-valent ferric ions (Fe Ⅴ+ ) were identified as active species. Therefore, researchers extensively exploited nonradical oxidation and have made great progress in persulfate-based nonradical activation process and nonradical mechanisms. At the same time, various catalysts are updated successively, but the summary of kinds of catalysts involved in nonradical oxidation is limited. Hence, we systematically summarized five nonradical oxidation mechanisms, and provided an elaboration on the recent development of sundry catalysts involved in nonradical oxidation in this review. The intrinsic impacts of carbon-based, metal-based materials are clarified, with emphasis on reactive oxygen species, pivotal functional groups and specific mechanism. For carbon-based catalysts, novel raw materials and special synthesis means are displayed. For latest metal-based catalysts like high-valent metal species (e.g., Fe(Ⅳ) and Mn(Ⅴ)), single-atom catalysts (SACs) and metal-organic frameworks (MOFs), we endeavored to present a critical understanding of the relationship between their structure and nonradical activation performance. Not only that, the particular mechanism of inorganics anions and organics were also illustrated in this paper. Lastly, we proposed the applications, opportunities and challenges of nonradical oxidation. Generally, this review provided a theoretical and applied research progress on nonradical oxidation and offered a comprehensive introduction for various catalysts involved in nonradical oxidation for better future research and environmental application. Graphical abstract: Graphical representation of the nonradical mechanisms for oxidation of organic pollutants in various catalytic systems Image 1